2021
DOI: 10.1089/tmj.2020.0223
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Telepractice in Speech Language Pathology in Hong Kong During the COVID-19 Pandemic

Abstract: Introduction: The aim of this study was to investigate the accelerated emergence of telepractice in speech language pathology during the coronavirus disease 2019 (COVID-19) pandemic in Hong Kong-a small city with limited accessibility concern that telepractice has not been widely implemented. Method: An online survey of speech therapists in Hong Kong was conducted between February and March in 2020. The survey comprised up to 15 questions to assess participants' demographics, existing service delivery in telep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
111
4
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(133 citation statements)
references
References 23 publications
7
111
4
11
Order By: Relevance
“…Additionally, telepractice has been deemed valid and effective by different professional organizations [10,11]. With the COVID-19 pandemic seriously disrupting the provision of speech and language therapy services, telepractice services have been increasingly adopted and regarded as the best option for delivering speech and language therapy during the pandemic [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, telepractice has been deemed valid and effective by different professional organizations [10,11]. With the COVID-19 pandemic seriously disrupting the provision of speech and language therapy services, telepractice services have been increasingly adopted and regarded as the best option for delivering speech and language therapy during the pandemic [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing adoption of telepractice in schools, various stakeholders have held different beliefs about telepractice. Although several surveys have shown that school-based speech-language pathologists doubt the efficacy of telepractice, others have revealed a positive attitude after using telepractice services [12,14,15]. However, parents' and children's perceptions of telepractice are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.12963/csd.20776 988 https://www.e-csd.org Na Yeon Kim, et al • Korean SLPs' Perception on Telepractice 게 엄청난 가능성을 열어줄 긍정적인 치료서비스임을 입증해 왔다 (Fong et al, 2020;Mashima et al, 2003;Tohidast, Mansuri, Bagheri, & Azimi, 2020). 구체적으로는 자폐스펙트럼장애, 언어발달장 애, 유창성장애, 말소리장애, 신경의사소통장애, 연하장애 등 다양 한 의사소통장애 유형에서 그 효과가 보고되었다 (Carey et al, 2010;Coufal, Parham, Jakubowitz, Howell, Reyes, 2018;Grogan-Johnson, Alvares, Rowan, & Creaghead, 2010;Grogan-Johnson et al, 2011;Lewis, Packman, Onslow, Simpson, & Jones, 2008;Morrell et al, 2017;Pullins & Grogan-Johnson, 2017;Weidner & Lowman, 2020).…”
unclassified
“…Los servicios de salud en el mundo debieron rápidamente implementar protocolos clínicos para la atención y rehabilitación de usuarios afectados por COVID-19 y, el fonoaudiólogo está teniendo un rol muy importante en la rehabilitación de secuelas post intubación en la deglución y motricidad orofacial. Paralelamente, las atenciones clínicas debieron ser reformuladas, existiendo reportes de telepráctica en fonoaudiología (Fong et al, 2020;Pamplona & Ysunza, 2020).…”
unclassified